Dari Catin ke Nifas: Pendampingan 7 Sasaran Berbasis Psikologi Perinatal untuk Mewujudkan Kondisi Fisiologis dan Kesejahteraan Ibu di Dusun Joho Sleman - Dwi Ratnaningsih; Amalina Tri Susilani; Harpeni Siswatibudi (Jurnal Pengabdian Masyarakat Permata Indonesia, 2026)
Maternal health is an important indicator of public health status, covering preconception, pregnancy, childbirth, and postpartum periods. A common issue is the lack of continuous assistance for pregnant women, postpartum mothers, and pre-marital couples, which may lead to complications. This community service activity aimed to improve physiological conditions through comprehensive assistance for pregnant women, postpartum mothers, and pre-marital couples in Joho Hamlet, Condongcatur, Sleman, on March 2–6, 2026. The method used was direct assistance through education, examination, monitoring, and counseling. The targets consisted of 7 individuals: 5 pregnant women, 1 postpartum mother, and 1 pre-marital couple. The results showed that all pregnant women had physiological pregnancies, the postpartum mother was in a physiological condition, and the pre-marital couple demonstrated good readiness. This assistance proved effective in improving sustainable maternal health. It is recommended that similar activities be conducted regularly with broader coverage.